A Web-Based Augmented Reality System - McNally, Kevin Francis; Koviland, Hoshang (EAI Endorsed Transactions on Scalable Information Systems, 2024)
Web-based augmented reality (AR) systems have many use cases and opportunities in Product Visualisation, Education and Training, Advertising and Marketing, Navigation and Wayfinding, Virtual Try-On, Interactive Storey Telling, Museums and Cultural Heritage, Training and Simulation, Gamification and more. As such, this research paper, A Web-Based Augmented Reality System, will explore these technologies and their use cases in the form of a literature review and several examples utilising the likes of Vectary, Blippar, Model Viewer and World Cast AR. The purpose of which, is to demonstrate a level of understanding of these virtual technologies, to develop them and to develop their future with practical use cases.
Keywords: AR; Web-Based AR; Vectary; Blippar; Model Viewer; World Cast AR